(3GdLeY Hjf GdUMjMjfs - (3GdCROj GdejhQbj GdnMpejOj, CHh YHO Gddg Hf CHj fUQ, GdMGpaX GdnMpejOj, eMeO Hf aqJhM Hf YHO Gddg Hf aJhM Hf MejO, (B488 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; dMeO ddg GdPj dG JMUi fYeg, hdG jJfGgi cQeg CeG HYO aEf Gddg JYGdi jbhd aj cJGHg GdefRd Ydi fHjg GdeQSd Udi Gddg Ydjg hSde(B: {(3cGf GdfGS CeI hGMOI aHYK Gddg GdfHjjf eHTQjf hefPQjf (B} (3hSCdJg GdYhf hGdJCjjO Ydi JLQjO eG aj gPjf GdcJGHjf ef eJhf GdCNHGQ hfUhU GdBKGQs
(3BNQgG (B:s
(3GdSGHY(B: (3Yf CHj GdNjQ Yf YbHI Hf YGeQ bGd hddHNGQj MOjK hGMO(B: (3Yf CHj GdNjQ bGd(B: (3CJjJ YbHI Hf YGeQ abdJ(B: (3CdG CYLHc ef CHj Jeje jQcY QcYJjf bHd UdGI GdeZQH abGd YbHI(B: (3EfG cfG faYdg Ydi YgO QShd Gddg Udi Gddg Ydjg hSde bdJ(B: (3aeG jefYc GdBf?s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 327s
3 / 583
(3cTa GdXfhf (B1 / 599s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdMOjK hGdeUWdMs